Assessment of Knowledge and Practices Toward COVID-19 Prevention Among Healthcare Workers in Tigray, North Ethiopia - Gebremeskel, Teferi G.; Kiros, Kalayu; Gesesew, Hailay A.; Ward, Paul R. (Frontiers in Public Health, 2021)
Background: The incidence rate of coronavirus disease 2019 (COVID-19) is increasing in several countries despite public health measures are put in place. Given COVID-19 is a newly emerging disease; there is little knowledge about the disease. The present study aims to assess knowledge, perception, and preventive practices towards COVID-19 among health workers in Tigray, North Ethiopia. Methods: A health facility-based cross-sectional study was conducted among health professionals working in public hospitals. Data were collected between Aprils to May 2020. The researchers included 403 participants and recruited them via a simple random sampling technique. To collect data, the researchers prepared a structured questionnaire guided by the WHO survey questions. The researchers applied descriptive and inferential statistical analysis. Tables and graphs were used to describe data, and multivariate binary logistic regression to determine factors affecting knowledge, perception, and practices towards COVID-19 prevention. Results: Among the participants, 79%, 88%, and 64.3% of them had adequate knowledge, positive perception, and good practice towards preventing COVID-19 respectively. Besides, 92% of the study participants knew that the COVID-19 virus does not have curative treatment and vaccine. The findings revealed that 55% of the respondents did not use the necessary personal protective equipment (PPE) at all times. The result showed that being female [AOR: 2.43, 95% CI (1.50-3.94)], work experience of 2-5 years [AOR: 2.44, 95% CI (1.10-5.39)]; news media as a piece of source information [AOR: 7.11, 95% CI (3.07-16.49)]; social media as a piece of source information [AOR:4.59, 95% CI (2.15-9.84)] and governmental website as a piece of source information [AOR: 4.21, 95% CI (2.15-8.27)] were reported as protective factors, and being single [AOR: 0.15, 95% CI (0.03-0.75)] was reported as risk factor toward the prevention of COVID-19. Conclusions: Most health workers had adequate knowledge and positive attitude towards COVID-19; nevertheless, a significant proportion of health workers had poor practice towards the prevention of COVID-19, including the use of PPE. Additionally, some groups of health professional showed poor practices of implementing the public health measures, a call to target at them to improve the prevention and control of COVID-19.